Machine-learned wearable sensors for real-Time hand-motion recognition: Toward practical applications - Pyun, Kyung Rok; Kwon, Kangkyu; Yoo, Myung Jin; Kim, Kyun Kyu; Gong, Dohyeon; Yeo, Woon Hong; Han, Seungyong; Ko, Seung Hwan (National Science Review, 2024)
Soft electromechanical sensors have led to a new paradigm of electronic devices for novel motion-based wearable applications in our daily lives. However, the vast amount of random and unidentified signals generated by complex body motions has hindered the precise recognition and practical application of this technology. Recent advancements in artificial-intelligence technology have enabled significant strides in extracting features from massive and intricate data sets, thereby presenting a breakthrough in utilizing wearable sensors for practical applications. Beyond traditional machine-learning techniques for classifying simple gestures, advanced machine-learning algorithms have been developed to handle more complex and nuanced motion-based tasks with restricted training data sets. Machine-learning techniques have improved the ability to perceive, and thus machine-learned wearable soft sensors have enabled accurate and rapid human-gesture recognition, providing real-Time feedback to users. This forms a crucial component of future wearable electronics, contributing to a robust human-machine interface. In this review, we provide a comprehensive summary covering materials, structures and machine-learning algorithms for hand-gesture recognition and possible practical applications through machine-learned wearable electromechanical sensors.
Keywords: Electro-mechanical sensors; Gestures recognition; Hand motion; Human Machine Interface; Machine learning algorithms; Machine learning techniques; Machine-learning; Motion recognition; Real- time; Soft electronics; artificial intelligence; gesture recognition; human-machine interfaces; machine learning; soft electronics; wearable sensor